1991
DOI: 10.1021/bk-1991-0467.ch016
|View full text |Cite
|
Sign up to set email alerts
|

Probes of the Lower Critical Solution Temperature of Poly(N-isopropylacrylamide)

Abstract: Cloud point, microcalorimetric, and fluorescent probe methods were in good agreement in determining the lower critical solution temperature (LCST) of an aqueous solution of a high molecular weight (Mn = 160,000), polydisperse (Mw/(Mn = 2.8) sample of poly(N-isopropylacrylamide) (PNIPAAM). The cloud point (32.2°C) concurred with the temperatures of abrupt changes observed in the emission spectra of micromolar quantities of solubilized fluorophores: the I1/I3 ratio of pyrene and the emission maxima of 1-pyreneca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…The NiPAM LCST in our hands were $ 27 8C (in phosphate buffer), lower than the commonly reported LCST of 30 ± 33 8C (in water) [25]. Obviously it needs to be lower than the physiological temperature of 37 8C and the difference between the polymer LCST and the physiological temperature is expected to determine the polymer dissolution rate in vivo.…”
Section: Discussioncontrasting
confidence: 69%
“…The NiPAM LCST in our hands were $ 27 8C (in phosphate buffer), lower than the commonly reported LCST of 30 ± 33 8C (in water) [25]. Obviously it needs to be lower than the physiological temperature of 37 8C and the difference between the polymer LCST and the physiological temperature is expected to determine the polymer dissolution rate in vivo.…”
Section: Discussioncontrasting
confidence: 69%
“…Even at 50°C, there is negligible settling observed for suspensions dosed with co-ionic PNIPAMs. The increase in settling rate that occurs when a suspension dosed with PNIPAM is heated above the LCST is a result of the phase separation attributed to the difference in free volume of the polymer and aqueous solvent [6,[31][32][33][34][35][36][37][38]. The polymer that has adsorbed on the surface at T below the LCST becomes insoluble as the temperature is raised and acts as a nucleation site for additional polymer deposition at T > LCST [4,39,40].…”
Section: Resultsmentioning
confidence: 99%
“…The earliest fluorescent probe studies showed that pyrene accumulated in the lower polarity domains [16] and the local polarity was slightly greater than methanol [17]. Similarly, FTIR has confirmed some hydrogen bonding to amide groups above the LCST [18].…”
Section: Discussionmentioning
confidence: 99%